Women in STEM in the Eastern Partnership: EU-Driven Initiatives and Challenges of External Europeanisation - Gabriela-Roxana Irod; Cristian Pîrvulescu; Marian Miculescu (Societies)
This article explores the role of the European Union (EU) as a normative gender actor promoting women’s participation in STEM (Science, Technology, Engineering, and Mathematics) within the Eastern Partnership (EaP) region. In a context marked by global inequality and overlapping international efforts, this paper assesses the extent to which EU-driven Europeanisation influences national gender policies in non-EU states. Using a postfunctionalist lens, this research draws on a qualitative analysis of EU-funded programmes, strategic documents, and a detailed case study encompassing Armenia, Georgia, Moldova, Ukraine, Belarus, and Azerbaijan. This study highlights both the opportunities created by EU initiatives such as Horizon Europe, Erasmus+, and regional programmes like EU4Digital and the challenges presented by political resistance, institutional inertia, and socio-cultural norms. The findings reveal that although EU interventions have fostered significant progress, structural barriers and limited national commitment hinder the long-term sustainability of gender equality in STEM. Moreover, the withdrawal of other global actors increases pressure on the EU to maintain leadership in this area. This paper concludes that without stronger national alignment and global cooperation, EU gender policies risk becoming symbolic rather than transformative.